Developing Quantum Games, Quantum Art, and Simulation Tools for Exploring Quantum Physics - Piispanen, Laura (My University, 2024)
This thesis presents five quantum physics-related game and art projects as annotated portfolios and practice descriptions created using Research through Design methodologies. It also describes the development of a numerical simulation tool for citizen science game development, which has been central to most of the described projects and influenced their design decisions. Additionally, another simulation tool was developed for educational and outreach purposes and is described alongside the project descriptions it connects to. Insights from these experiences led to the design guidelines of quantum physics-related games shared in this thesis. Quantum physics, a well-established theory describing our world's fundamental aspects, has inspired the creators of games for decades. Many of them have been researchers and educators, but the rise of quantum physics-themed game jams, hackathons, and courses has broadened the audience creating these games, and the online accessibility of quantum computers has further led to the emergence of “quantum computer games”, games on quantum computers. These “quantum games” include video games, VR games, board games, and card games with varying references to quantum physics. Despite over 300 categorised quantum games, discussions on their development practices are limited. The increase of attention to the serious use of quantum games by a variety actors highlights this shortcoming. To address this, this thesis provides practical design guidelines for collaborative projects integrating quantum physics expertise. These guidelines emphasise early, collaborative inclusion of expertise, clear communication of design decisions, the use of playable prototypes and carefully curated visual language in team communication, and strategic use of simulation tools to facilitate successful development. By providing insights into the challenges, opportunities, and best practices of quantum game development, the thesis promotes broader discussions on interdisciplinary science game development and their use in education, scientific communication, and public engagement. The insights shared in this thesis are applicable to various fields related to quantum technology.

Tämä opinnäytetyö esittelee viisi kvanttifysiikkaan liittyvää peli- ja taideprojektia kommentoitujen portfolioselostusten ja käytäntökuvausten muodossa, jotka on luotu Tutkimus muotoilun kautta -menetelmällä (engl. Research through Design). Lisäksi se avaa kansalaistiedepelejä varten luodun numeerisen simulointityökalun kehitystä. Tämä työkalu on ollut keskeinen osa useimpia esitellyistä projekteista ja vaikuttanut niiden muotoilupäätöksiin. Lisäksi kahteen esitellyistä töistä liittyy toinen, yleissivistämis- ja opetustarkoituksiin kehitetty simulointityökalu, joka esitellään näiden töiden yhteydessä. Näistä kokemuksista rakentuu tässä opinnäytetyössä jaetut kvanttifysiikkaan liittyvien pelien kehitysohjeistukset. Kvanttifysiikka on maailmamme peruspalasia kuvaava, vakiintunut teoria, joka on inspiroinut myös alan tutkijoiden kehittämiä pelejä. Kvanttifysiikka-aiheisten pelijamien, hackathonien ja pelikehityskurssien yleistyminen on kuitenkin inspiroinut laajempaa yleisöä luomaan kvanttifysiikasta inspiroituneita pelejä. Ensimmäisten kvanttitietokoneiden saatavuus verkon yli on johtanut “kvanttitietokonepelien” kehitykseen, peleihin kvanttitietokoneilla. Kaikkiin edellä esiteltyihin viittaamme sanalla “kvanttipelit”. Kvanttipelejä on kehitetty videopeleiksi, virtuaalitodellisuuspeleiksi, lautapeleiksi ja korttipeleiksi, ja vaikka yli 300 peliä on luokiteltu kvanttipeleiksi, keskustelut näiden pelien kehityskäytännöistä ovat edelleen rajallisia. Kiinnostus kvanttipelien hyötykäyttöön on saavuttanut eri tahojen kasvavan kiinnostuksen, mikä puolestaan alleviivaa tätä puutetta. Tämä opinnäytetyö tarjoaa käytännöllisiä kehitysohjeistuksia projekteille, joissa hyödynnetään kvanttifysiikan asiantuntemusta. Nämä ohjeet korostavat asiantuntijoiden varhaista ja yhteistyöhön perustuvaa mukaan ottamista, selkeää suunnittelupäätösten viestintää, pelattavien prototyyppien käyttöä ja huolellisesti valitun visuaalisen kielen käyttöä tiimiviestinnässä sekä simulaatiotyökalujen strategista hyödyntämistä onnistuneen kehityksen edistämiseksi. Jakamalla näkemyksiä kvanttipelikehityksen haasteista, mahdollisuuksista ja parhaista käytännöistä se edistää laajempaa keskustelua monitieteisestä tieteen pelien kehittämisestä ja niiden hyödyntämisestä koulutuksessa, tieteellisessä tiedotuksessa ja suuren yleisön osallistamisessa. Opinnäytetyön tarjoamat oivalluksia ovat sovellettavissa monilla kvanttiteknologiaan liittyvillä aloilla.
Keywords: quantum games, quantum mechanics, game development, quantum game jam